The Shift of Honorifics due to The Promotion As A Government Official: Comparative Study - Sukmawaty Sukmawaty; Citra Andini; Fakhriawan Fathu Rahman (Hasanuddin University, 2022)
The general public claims that there are socially agreed rules of honor and that the use of honorary titles is a matter of complying with those rules, and researchers often claim this too. This research aims to identify the kinds of the honorifics used by English and Buginese Bone language, and to analyze the use of the honorific in used English and Buginese Bone focused on the shift of honorifics due to the promotion as a government officer. This was comparative study between English and Buginese language in respect someone in order to highlight the social status and rank of job and to show respect and to dignify social status. This research used the descriptive qualitative method while the English data were obtained through the English movies that are Black Widow, and The Intern, as well as the news posted at BBC news.com about people who receive awards in the form of titles while Buginese data were obtained through the participants recording and note-taking. The research result show that in English almost every year the country's leaders give royal titles to people who excel in their respective careers, and the title is recognized by the state, the title